PERANCANGAN SISTEM INFORMASI PENDAFTARAN PASIEN UNIT GAWAT DARURAT DI RUMAH SAKIT LANUD SULAIMAN BANDUNG - Rofi Nuraziz Rusmiyandani; Dety Mulyanti (Jurnal Anestesi, 2023)
EMERGENCY UNIT PATIENT REGISTRATION INFORMATION SYSTEM DESIGN IN LANUD SULAIMAN BANDUNG HOSPITAL This research aimed to know emergency unit patient registration information system design in Lanud Sulaiman Bandung Hospital. The method was descriptive qualitative method approach to data collection techniques were direct observation, interview and literate studies that had relevance to the subject matter of research problem. The problems that hinder the process of registration in the emergency department included: 1). Processing Installation Emergency Unit registration report as a whole was still done manually and not structured; 2). Installation Emergency Unit type of service structured not yet, so many patients who were not emergency services who came to the Emergency Unit. The suggestions were given to the optimization process of emergency unit registration at Lanud Sulaiman Bandung Hospital, there were: 1). Coordination to the Head of Medical Records and Head of the Hospital for the addition of a registration officer in the emergency unit and supporting facilities such as computer information systems; 2) The hospital provides information such as notice boards or brochures about the schedule of doctors in the hospital.